Study the polyphenolic compounds composition of Thymus vulgaris L. herb - Mazulin, O. V.; Fukleva, L. A.; Mazulin, G. V.; Мазулін, Олександр Владиленович; Фуклева, Лариса Анатоліївна; Мазулін, Георгій Владиленович (Запорізький державний медичний університет, 2023)
The aim of the work is to determine the accumulation of polyphenolic compounds in Thymus vulgaris L. herb at the end of flowering using TLC and HPLC methods. Materials and methods. For experimental studies, alcohol extracts from Thymus vulgaris L. herb (1:100) were used. The plants were cultivated in Volodymyrivka, Zaporizhzhia region during the period of maximum polyphenolic compounds accumulation (June – August 2022). The substances’ component composition was studied by TLC method Biostep CD 60 densitometer (Germany) and HPLC Agilent 1260 Infinity HPLC System Open LABCDS Software (Japan). Results. TLC and HPLC methods revealed up to 29 polyphenolic compounds. Experimentally determined flavonoids and hydroxycinnamic acids are known in phytotherapy for their pronounced anti-inflammatory, antimicrobial, and antioxidant activities. Мета роботи – за допомогою методів тонкошарової хроматографії (ТШХ) та високоефективної рідинної хроматографії (ВЕРХ) визначити накопичення поліфенольних сполук у траві чебрецю звичайного під час цвітіння. Матеріали та методи. Для експериментальних досліджень використали спиртові витяги з трави чебрецю звичайного (1:100), культивованого в c. Володимирівка Запорізької області (Україна) під час максимального накопичення поліфенольних сполук (червень – серпень 2022 року). Компонентний склад речовин досліджували методом ТШХ на денситометрі Biostep CD 60 (Німеччина) та ВЕРХ на хроматографі Agilent 1260 Infinity HPLC System Open LABCDS Software (Японія). Результати. Методом ТШХ і ВЕРХ ідентифіковано 29 сполук поліфенольної природи. Експериментально визначено вміст біологічно активних речовин (флавоноїди, гідроксикоричні кислоти), що відомі в фітотерапії вираженою протизапальною, протимікробною, антиоксидантною діями.
Визначення накопичення поліфенольних сполук у траві чебрецю звичайного (Thymus vulgaris L.)
Mazulin O. V. - ORCID ID: 0000-0003-0628-4457; Fukleva L. A. - ORCID ID: 0000-0002-2930-0619; Mazulin G. V. - ORCID ID: 0000-0002-4227-7388.
Keywords: Thymus vulgaris L.; TLC; HPLC; medicinal herb; anti-inflammatory activity; antimicrobial activity; antioxidant activity; чебрець звичайний; ТШХ; ВЕРХ; лікарська рослина; протизапальна активність; протимікробна активність; антиоксидантна активність